Maritime Poetics From Coast to Hinterland - Gee, Gabriel N.; Wiedmer, Caroline (Edition Kulturwissenschaft, 2021)
In the past fifty years, port cities around the world have experienced considerable changes to their morphologies and their identities. The increasing intensification of global networks and logistics, and the resulting pressure on human societies and earthly environments have been characteristic of the rise of a »planetary age«. This volume engages with contemporary artistic practices and critical poetics that trace an alternate construction of the imaginaries and aspirations of our present societies at the crossroads of sea and land - taking into account complex pasts and interconnected histories, transnational flux, as well as material and immaterial borders.